Cardiovascular outcomes in patients with left atrial enlargement undergoing transcatheter aortic valve implantation. Issue 6 (16th February 2022) - Asami, Masahiko; Dobner, Stephan; Stortecky, Stefan; Heg, Dik; Praz, Fabien; Lanz, Jonas; Okuno, Taishi; Tomii, Daijiro; Reineke, David; Windecker, Stephan; Pilgrim, Thomas
Abstract: Background: Increased left ventricular afterload resulting from severe aortic stenosis (AS) leads to progressive cardiac remodeling. Left atrial enlargement (LAE) is an early manifestation in a series of maladaptive changes and may affect clinical outcomes after valvular replacement therapy. The aim of this study is to determine the impact of LAE on clinical outcomes in symptomatic patients with severe AS undergoing transcatheter aortic valve implantation (TAVI). Methods: In a prospective single‐center TAVI registry, we analyzed LA dimensions measured by echocardiography before intervention. Patients with atrial fibrillation or concomitant mitral valve disease were excluded. LAE was defined as indexed LA volume >34 ml/m 2 . The primary endpoint was cardiovascular death (CVD) at 1 year. Results: Among 1663 patients undergoing TAVI between August 2007 and December 2016, 768 (46.2%) were eligible for the present analysis and 486 patients had LAE. The prevalence of LAE was higher in males (68.3%) as compared to females (58.8%). Patients with LAE were older (82.3 ± 6.7 years vs. 80.0 ± 6.4 years) and had a higher STS‐PROM score (6.1 ± 4.7% vs. 4.7 ± 2.9%). After adjustment, patients with LAE had an increased risk of CVD at 1‐year compared to patients with normal LA dimensions (49 [10.4%] vs. 8 [2.9%]; HRadj, 3.52; 95% CI, 1.66–7.44)]. In multivariable analysis, LAE was independently associated with an increased risk of CVD at 1‐year (HRadj, 3.52; 95% CI, 1.66–7.44). Conclusions: LAE secondary to AS was documented in a significant proportion of patients undergoing TAVI and was associated with a more than threefold increased risk of CVD at 1‐year.